(untitled) (Research, Society and Development, 2020)
New food ingredients have been researched to satisfy the demands of consumers, seeking to obtain products with sensory and nutritional quality associated with health benefits. In this sense, the present work aimed to use green banana biomass, carob and chia as ingredients in the formulation of gluten and lactose-free brownie. Thus, a 22 factorial design was used, with two variables, concentration of chia and carob chocolate, obtaining four formulations. A market research was applied in order to know the possible consumer audience and the color parameters were evaluated using the CIE L*a*b* system, texture, with the aid of a texturometer evaluating the softness by compression and sensory analysis, through the hedonic scale. Through market research it was found that the consumer profile of the proposed product was satisfactory, where 77.3% of the participants were in favor of its consumption. The texture was similar in all formulations (p≤0.05), ranging from 8.80 to 9.26 N. Evaluating the data obtained for color, it was possible to verify that the samples were dark based on the luminosity (L*) and for a* and b* in the red and yellow regions, a combination that results in brown coloring. The results of the sensory analysis indicated that there was no significant difference (p≤0.05) for any of the evaluated attributes (color, flavor, aroma, texture and overall appearance), and an excellent acceptance index, greater than 70%, was obtained.